Bioengineered potato: Resistance to late blight disease and higher crop yields - Ghislain, Marc; Barekye, Alex (International Potato Center, 2019)
Average potato yields in sub-Saharan Africa are four times lower than those in industrialized nations, mostly due to the effects of diseases, particularly late blight. This research demonstrates that the transfer from wild potato relatives of three resistance-conferring genes into a cultivated potato variety provides complete resistance to late blight for several seasons. Initial findings suggest this resistance will be long lasting. Cultivation of this late blight resistant potato would increase family farm incomes by 40% and ensure the supply of fungicide-free potatoes to consumers.